Associations between intakes of individual nutrients or whole food groups and non‐alcoholic fatty liver disease among Korean adults. Issue 6 (June 2014) - Han, Jung Mi; Jo, An Na; Lee, Seung Min; Bae, Hyun Suk; Jun, Dae Won; Cho, Yong Kyun; Suk, Ki Tae; Yoon, Jai Hoon; Ahn, Sang Bong; Cho, Yong Jin; Kim, Seong Woo; Jang, Eun Chul
Abstract Background and Aim Dietary factors are closely associated with the risk of non‐alcoholic fatty liver disease (NAFLD). Asian and Western diets differ in energy‐nutrient composition, fatty‐acid composition, and main nutritional sources; therefore, the implications would be limited if the Western‐oriented study results were applied to Asian patients. We aimed to identify the nutrient and food group intakes of a typical Asian diet and assess their effects on NAFLD risk. Methods In total, 348 subjects were recruited from 5 participating hospitals. Information on sociodemographic characteristics and health‐related behaviors were obtained through face‐to‐face interviews. NAFLD was diagnosed by ultrasound. Dietary intakes were assessed with a 24‐h recall applying a multiple‐pass approach and 4‐day food records that included 1 or 2 weekend days. Results There were no significant differences in health‐related behaviors between the cases and controls except for smoking behavior. The cases had elevated triacylglycerol, fasting glucose, and low‐density lipoprotein cholesterol levels compared with the controls. In men, after adjusting for variables, low intakes of vitamin C (odds ratio [OR], 4.23), vitamin K (OR, 3.93), folate (OR, 3.37), omega‐3 fatty acids (OR, 2.16), and nuts and seeds (OR, 3.66) were associated with a significantly higher risk for developing NAFLD. In women, vitamin K (OR, 2.54) and vegetable (OR, 4.11) intakes showed a significant beneficial effect for lowering NAFLD risk. Conclusions Adequate intakes of vitamin C, vitamin K, folate, omega‐3 fatty acids, nuts and seeds, and vegetables may help in preventing NAFLD in Korean adults.